2000
DOI: 10.1892/0891-6640(2000)014<0125:iidacf>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Infection in Dogs and Cats: Facts and Fiction

Abstract: The discovery of the spiral bacterium Helicobacter pylori and its causative role in gastric disease in humans has brought a dramatic change to gastroenterology. Although spiral bacteria have been known for more than a century to infect the stomachs of dogs and cats, recent research has been conducted mainly in the wake of interest in H. pylori. H. pylori has not been found in dogs and only very rarely in cats and zoonotic risk is minimal. A variety of other Helicobacter spp. can infect the stomach of pets; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 73 publications
6
71
1
5
Order By: Relevance
“…were seen in the mucus, over the tissue surface, at the crypt bottom and inside the gastric glands, adding that in this research the bacteria density was higher in areas with more mucus 6,7 .…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…were seen in the mucus, over the tissue surface, at the crypt bottom and inside the gastric glands, adding that in this research the bacteria density was higher in areas with more mucus 6,7 .…”
Section: Discussionsupporting
confidence: 59%
“…are frequently found in dogs [6][7][8]15 , not only in healthy animals 15 , but also in dogs with gastropathy simptoms 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An early study used several detection techniques and showed that the stomach of 91% of pet cats (n=58) were positive for the genus Helicobacter (Neiger et al 1998), suggesting a high occurrence of this bacterial group in the feline stomach. In another study, it was shown that cats and dogs are predominantly coloniszed by H. heilmannii (Priestnall et al 2004) but other species (e.g., H. felis, H. bizzozeronii, H. salomonis, H. pametensis) have also been identified in these animal species (Neiger and Simpson 2000).…”
Section: The Gi Microbiota Of Catsmentioning
confidence: 99%